Intravenous Thrombolysis Benefits Mild Stroke Patients With Large-Artery Atherosclerosis but No Tandem Steno-Occlusion - Wang, Dapeng; Zhang, Lulu; Hu, Xiaowei; Zhu, Juehua; Tang, Xiang; Ding, Dongxue; Wang, Hui; Kong, Yan; Cai, Xiuying; Lin, Longting; Fang, Qi (Frontiers in Neurology, 2020)
At present, there is controversy regarding whether thrombolysis is beneficial for patients suffering from a mild stroke. In this study, we therefore sought to determine whether the therapeutic benefit of thrombolysis is dependent upon stroke subtype for those with mild stroke. We conducted a retrospective analysis of data from consecutive mild stroke patients (National Institutes of Health Stroke Scale ≤5) with and without recombinant tissue plasminogen activator (rt-PA) therapy. The TOAST (Trial of Org 10172 in acute stroke treatment) criteria was used to determine stroke subtypes. Patients suffering from large-artery atherosclerosis (LAA) were subdivided based upon whether or not they exhibited tandem steno-occlusion, as defined by the association of a proximal intracranial occlusion and a cervical internal carotid artery lesion (complete occlusion or severe stenosis ≥ 90%). For this study, favorable outcomes at 90 days of onset (modified Rankin Scale Score [mRS] of 0 - 1) were the primary measured outcome. 339 patients were included in the study. For patients with non-LAA, there were not statistically significant improvements in favorable outcomes for rt-PA treatment (p = 0.889, 0.929, 0.708; respectively). For patients with LAA, compared with non-treated group, rt-PA-treated patients had a significant in the rate of favorable outcomes at 90 days (82.8% vs 64.9%; OR 2.59; 95%CI, 1.13-5.92; P=0.024). Among LAA patients exhibiting tandem lesions, favorable outcomes were observed in 66.7% of rt-PA-treated patients, with no significant differences to those observed in untreated patients (OR 1.00; 95%CI, 0.23-4.28; p = 1.000). Among LAA patients without tandem lesions, compared with non-treated group, we found that rt-PA treatment was associated with a significant beneficial impact on favorable outcomes after 90 days (64.4% vs. 88.4%; OR 4.20; 95%CI, 1.43-12.30; p = 0.009). Our findings suggest that intravenous rt-PA is only beneficial in mild stroke patients with LAA-type strokes that do not exhibit tandem steno-occlusion.